Hislopathalogical Changes in the Testes and Epididymis of Mice Fed with Cadmium Chloride - Kadhim, A.H.; Al-Bairuty, J.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The  present   research   was  conducted   to  determine   the  effect  of Cadmium   Chlori de  on  the  t  stes  and  epididymis  of  white  mice  fed with  diffl rent  concentration     (75,  1 00 150  ppm)  of this hea  y metal for three,   ix and nine days. The r   ults showed  that cadm i um chloride caused   s  vera!  histopathalogical  change in  testes  and  epidid   mis in  luding deg  neration and cell necrosis  in addition  to the appearanc of  haemorrhage and o  dema  in the tissues . It was clear that the effect increased  in r  lation with the concentration and the treatment  period.